Assessment of material properties of AISI 316L stainless steel using non-destructive testing. Issue 4 (1st October 2016) - Khan, Sohaib Z.; Khan, Tariq M.; Joya, Yasir F.; Khan, Muhammad A.; Ahmed, Sarah; Shah, Aqueel
Abstract: Ultrasonic testing (UT) is one of the most widely used non-destructive testing techniques for the characterisation and the evaluation of materials. In this work, material properties of AISI 316L stainless steel are assessed using UT. Changes in ultrasound velocity, attenuation and hardness are observed in heat-treated material at different temperatures. Specimens analysed at granular level through optical and scanning electron microscope exhibited change in the grain structure at various heat treatment temperatures. It was observed that the change in grain size also affected the mechanical vis-à-vis ultrasonic properties. In conclusion, the empirical results are also deduced in form of a relationship between UT parameters and mechanical properties of the material.